THE BOYSCOUT ACTIVITIES MANAGEMENT TO ENHANCING PUBLIC MIND OF KHUNTHALE SCHOOL NETWORK UNDER SURATTHANI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Fueangfung, Kallayanee; PhrakhruPhichitsupakarn; Yotharak, Maliwan (Journal of Educational Review Faculty of Education in MCU, 2025)
The objectives of this study were 1) to study the conditions of the boy scout activities management to enhancing public mind of Khunthale school network under Suratthani Primary Educational Service Area Office 1. 2) to study the guidline for the boy scout activities management to enhancing public mind of Khunthale school network under Suratthani Primary Educational Service Area Office 1. 3) to present the guidelines for the boy scout activities management to enhancing public mind of Khunthale school network under Suratthani Primary Educational Service Area Office 1. This qualitative research was collected data by using in-depth interview with 15 involved persons about the participation condition, 5 experts in guidelines creation and 7 experts by using focus group discussion to evaluate feasibility, suitability, and utility. Qualitative data were analyzed using content analysis. The results of the study were as follows: 1) The conditions of the boy scout activities management to enhancing public mind of Khunthale school network under Suratthani Primary Educational Service Area Office 1, the research revealed that the administration of Scout activities did not follow the sequence specified in the Scout - Girl Guide manual. There was no solicitation of feedback, discussions, or reflections on the issues, strengths, and areas for improvement of the activities, resulting in inadequate development of Scout activities administration. Effective administration required the cooperation of administrators, teachers, and related personnel to focus on improvement, guidance, promotion, development, and systematic steps to achieve the school’s set goals. The Scout activities included camping activities, community service and public benefit activities, school development activities, religious place development activities. 2) The guideline for the boy scout activities management to enhancing public mind of Khunthale school network under Suratthani Primary Educational Service Area Office 1, the guidelines for promoting volunteer spirit included (1) A shared vision, (2) Unity and teamwork, (3) Participation in social activities, (4) Public responsibility, (5) Respect and honor for others. 3) The results of the guideline for the boy scout activities management to enhancing public mind of Khunthale school network under Suratthani Primary Educational Service Area Office 1, the results indicated that the guidelines for the boy scout activities management to enhancing public mind of Khunthale school network under Suratthani Primary Educational Service Area Office 1 were feasible, appropriate, and beneficial for managing scout activities to promote the volunteer spirit within the educational institutions.